Implementation Of Differentiated Learning In Improving Geography Understanding Through The Decision Tree Model In High School - Yusi Sri Mulyani; Arnie Fajar; Lili Halimah (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the implementation of differentiated learning in improving students' understanding of geography subjects through the Decision Tree model. The research uses a qualitative approach with a case study method at SMA Negeri 1 Cililin, West Bandung Regency. The research subjects consisted of school principals, vice principals for curriculum, geography teachers, and students. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis uses an interactive model through data reduction, data presentation, and conclusion drawn. The results of the study show that: (1) learning planning is carried out through diagnostic assessments to identify students' readiness, interests, and learning profiles; (2) the Decision Tree model assists teachers in determining content, process, and product differentiation strategies; (3) the implementation of learning is more varied, flexible, and student-centered; and (4) differentiated learning increases student engagement and understanding of geography concepts. This study concludes that differentiated learning integration with the Decision Tree model is effective in creating adaptive and meaningful learning.